Eristic techniques in the literary model of dispute: Ivan Turgenev’s chosen novels - Olaszek, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The subject of discussion in the present paper is the model of the dispute as a speech genre created by Ivan Turgenev. Special attention is paid to eristic techniques of disputation. Eristic techniques (those proposed by Schopenhauer) determine the intention of a dispute aimed not at establishing the truth, but at convincing the addressees of the validity of argumentation presented by certain disputants. An analysis of the course of the disputes in Turgenev’s novels allows us to notice the use of many eristic techniques, in particular, the shifts of emphasis from the subject of the dispute (ad rem) to the disputing persons (ad personam). It proves that the writer focuses on pointing to the forces that can lead Russia towards a better future, rather than on looking for a way of solving problems. A positive characterization of the moderate disputants, while not of the fierce ones, allows for a more precise conclusion: Turgenev was a supporter not of eternal disputes but of dialogue and compromise.